Pengaruh Kualitas kerja dan Pengawasan Terhadap Kinerja Pegawai Yakes Telkom Makassar - Nuraira Rahman; Asdi; Nurinaya (Jurnal Ilmiah Manajemen Emor (Ekonomi Manajemen Orientasi Riset), 2024)
This study aims to determine the effect of work quality and supervision on the performance of Yakes Telkom Makassar employees. This research was conducted using quantitative approach methods and data collection techniques through questionnaires. This study used a non-probability sample, namely a saturated sample, where all populations were sampled, namely 32 respondents at Yakes Telkom Makassar. The analytical technique used in this study is an attractive model with respondents, where the interpratation data is then regulated using data analysis techniques in this case SPSS The results of this study show that the variable of work quality (X1) has a positive and significant effect on the performance of Yakes Telkom Makassar employees, showing that the better the quality of employee work, the better the performance of employees in completing the tasks given. Supervision (X2) did not have a positive and significant effect on employee performance, showing that even though supervision was not carried out on the employee kinerj, they were still able to complete the work given.